THE ROLE OF ISLAMIC lJTIHAD IN THE REGULATION AND CORRECTION OF CAPITAL MARKETS (American Journal of Islam and Society, 1997)
I am hesitant to speak on the role of ijtihiid in an Islamic capital market,because this topic requires understanding two important but difficultareas whose primary sources are in different languages. The first area isijtihiid which is connected withfiqh issues; the majority of its sources arein Arabic. The second area is economics which is connected with theanalysis of capital markets; the majority of its sources are in Europeanlanguages. Linking ethics and economics is necessary but difficult.Necessary, because every economic choice has a spiritual dimension.Difficult, because secular economics severs the link, by reducing valuesto tastes and arguing that different ethical values do not change themethod of choice. Therefore, properly linking ijtihiid and economics is adifficult task, requiring determined effort to refute the secular separationof ethics and economics. I spent over 100 hours thinking, reading, andanalyzing the essential points of both until I could establish commonground between them.Ijtihad is of central importance in usul al-fiqh, and concerns themethod of implementing the spirit of the sacred texts in any environment.Since the third century A.H., ijtihd has been the main theme ofdialog between the different schools of fiqh. To this day scholars debatethe issue.Economics is an important science in our time, influencing severalother sciences. Since the capital market is a significant topic in economics,it is important to understand the strengths and weaknesses of the neoclassicalanalysis of capital markets' in developing an Islamic capitalmarket. We must also understand the history of economic thought, howcapital markets became an important part of it, and why many ...